Negotiating the Boundary of Unconditional Surrender: The War Refugee Board in Sweden and Nazi Proposals to Ransom Jews, 1944–1945 - Hindley, Meredith (Holocaust and genocide studies, 1996)
In 1944–45, Iver Olsen, special representative of the United States War Refugee Board in Sweden, became the recipient of a series of proposals to exchange Jews for cash or matériel. The proposals, which were supposedly extended for humanitarian reasons, represented an attempt by highranking Nazi officials, notably Heinrich Himmier, to open a dialogue with the Americans on a separate peace. Constrained by limits of the Allied policy of unconditional surrender, Olsen and American Minister Herschel Johnson attempted to aid Jews, but the political ramifications of concluding a deal prevented an exchange.